Statistics as an Essential Element of Modern Hybrid Warfares - M. V. Karmanov (Статистика и экономика)
The relevance of the study lies in the fact that at present, information flows, often based on “falsification” of data, are having an increasing influence. And statistics act as such a tool.Purpose of the study. The purpose of this paper is to study opinions and approaches to the use of statistics to conduct information wars.Materials and methods. The study examined the main directions of statistics as a tool for working with data. The most common and practically justified is the use of statistics as a tool of knowledge, management, propaganda and control. The result of interpreting statistical data primarily depends on the degree of objectivity and level of literacy of those who work with the data: both at the initial stage of the original data array, and at the stage of explaining the resulting values.Results. It was revealed that the same parameters (proportions) can be interpreted in completely different ways. Such differences arise both from the subjectivity of the perception of these data and from the degree of elaboration of the material. As a result, a field for discrepancies and discussion arises.Conclusion. Statistics have already become an integral component of wars of a new format, where the battle for people’s worldview becomes the basis for further presence in many spheres of life. But with competent, properly structured and timely statistical information, it is possible to suppress falsely generated data and inflict damage on the enemy that significantly exceeds direct military clashes on the battlefield.